Understanding Children's Behaviour - Jayson, Dinah (Poole Family Doctor Publications, 2005)
Designed and written specifically for the general reader, the books in this series provide essential reading for sufferers and those who seek to understand and support them. This title focuses on children's behavior.
Include Color Illustrations, Tables and Index
Keywords: Child psychology -- Behavior disorders in children -- Child development